Association between TMPRSS2 rs2070788 polymorphism and COVID-19 severity: a case-control study in multiple cities of Iran - Faridzadeh, Arezoo; Mahmoudi, Mahmoud; Rahimlou, Bahman; Naghizadeh, Mohammad Mehdi; Ghazanfari, Tooba (Frontiers in Medicine, 2024)
Introduction Host genetic variations have been identified as potential influencers of COVID-19 infection. This study aimed to examine the association between transmembrane serine protease type 2 (TMPRSS2) rs2070788 single nucleotide polymorphism (SNP) and the prognosis of COVID-19 in Iranian populations. Method This case-control study was performed on 756 COVID-19 patients and 59 healthy individuals across Iran. Clinical data, blood samples, and the presence of the TMPRSS2 rs2070788: G>A SNP were determined using T-ARMS-PCR. Additionally, serum levels of tumor necrosis factor α (TNF-α), C-reactive protein (CRP), interleukin-6 (IL-6), and IL-1β were evaluated in the collected blood samples. Results No significant association was found between the genotypes and allele frequencies of TMPRSS2 rs2070788 SNP and susceptibility to or mortality from COVID-19 infection. However, we observed a substantial increase in IL-6 and CRP levels associated with the severity of COVID-19, while no such trend was observed for IL-1β and TNF-α. This study showed a considerable rise in TNF-α and IL-1β serum levels exclusively in COVID-19 patients with TT rs2070788 TMPRSS2 SNP genotype compared to healthy controls. Conclusion In this study conducted across multiple cities in Iran, no significant association was found between the TMPRSS2 rs2070788 SNP genotypes and COVID-19 severity or mortality.